Multiple myeloma: Periapical location can challenge diagnostic skills - M B Radhika; Lalita J Thambiah; K Paremala; M Sudhakara (Wolters Kluwer Medknow Publications, 2010)
Multiple myeloma is a relatively rare malignant hematological disease, which is characterized by multicentric proliferation of plasma cells in the bone marrow and radiographically by osteolytic bone lesions and detectable presence of monoclonal immunoglobulins in serum and/or urine. Diagnosis of multiple myeloma can sometimes be challenging because of its plethora of clinical signs and symptoms. The product of the malignant plasma cells causes the different types of unusual clinical manifestations. We present the case of a 55-year-old female who presented with a periapical swelling in anterior maxilla in relation with 11 as the first sign of the disease.